Reading the Bibliographies of the Women’s Rest Tour Association: Cultural Travel in the Long Nineteenth Century - Julia Carlson (Transatlantica)
The Boston-based Women’s Rest Tour Association provided a carefully selected reading list for its “literary pilgrims” from its founding in the 1890s into the twentieth century. As an organization designed to support educated American women traveling on a budget, the WRTA provided members with a range of information to facilitate travel, including a handbook containing two lengthy bibliographies. These bibliographies expose a duality within the organization that balances a progressive feminism with a deep-seated cultural and social conservatism. They exhibit strong support for women writers and educational reading as a tool for personal empowerment at the same time that they show a commitment to the cultural authority of Boston and the British Isles and reveal a notable degree of class bias and ethnic prejudice.